Nigeria : medium-term research plans, 1996-2000 - Shaib, B.; Aliyu, Adamu; Bakshi, J. S.; Federal Ministry of Agriculture and Natural Resources, Nigeria (Abuja, Nigeria : Dept. of Agricultural Sciences, Federal Ministry of Agriculture and Natural Resources, 1997)
This volume contains the medium-term research plans, which forms the integral part of the National Agricultural Research Strategy Plan and cover the first 5-year period, 1996-2000.
Includes bibliographical references.
lje 20/3/19
Arch.
Keywords: Agriculture